Weight optimization of leaf spring assembly using design for manufacturing approach and FEM in graduated leaves for Electric Vehicle - Khan, Mohammed Irfan; Soni, Shubham; Patel, Anil; Nayak, Chitresh (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this study is to determine the ideal stress distribution for a multi-leaf spring assembly using finite element analysis. Furthermore, the topology enhanced model, based on associate load is included in this research work. This work is carried out by considering two different techniques involving design for manufacturing (DFM) after the attainment of results from topology optimization.
Keywords: multi-leaf spring; finite element method; topology optimization; electric vehicles